2014
DOI: 10.11646/zootaxa.3895.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial phylogeography and intraspecific taxonomy of the Steppe Racerunner, Eremias arguta (Pallas) (Lacertidae: Sauria, Reptilia), reflects biogeographic patterns in Middle Asia

Abstract: Steppe racerunner, Eremias (Eremias) arguta, is one of the most widespread species of the Asian racerunners (genus Eremias). Several subspecies were traditionally recognized however, morphological variability is so high that delimitation of these subspecies was always problematic. Here we present a phylogenetic hypothesis for this species based on cytochrome b sequences (55 samples from 35 populations, 900 bp partial sequences), infer it biogeography and the revise its subspecific structure. Six major phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…From many forms of Eremias described between XIXʹXX centuries as a result of the Central Asian expeditions carried out by Nikolay Przewalski and his followers, the comprehensive monograph of Szczerbak (1974) recognized as valid species only E. multiocellata, E. przewalskii, E. buechneri, E. quadrifrons from Central Asia and E. argus and E. brenchleyi from Eastern Asia. In his monograph, Szczerbak (1974) discriminated Eremias taxa mostly using mean character values for large sample sizes grouped a priori to geographic populations and thus many local variations remained unnoticed in his analysis (Poyarkov et al 2014). However, even morphologically "good" species in Central Asian Eremias are often difficult to diagnose due to high ecological and geographic variation of characters and presence of numerous "intermediate" forms and populations.…”
Section: Discussionmentioning
confidence: 99%
“…From many forms of Eremias described between XIXʹXX centuries as a result of the Central Asian expeditions carried out by Nikolay Przewalski and his followers, the comprehensive monograph of Szczerbak (1974) recognized as valid species only E. multiocellata, E. przewalskii, E. buechneri, E. quadrifrons from Central Asia and E. argus and E. brenchleyi from Eastern Asia. In his monograph, Szczerbak (1974) discriminated Eremias taxa mostly using mean character values for large sample sizes grouped a priori to geographic populations and thus many local variations remained unnoticed in his analysis (Poyarkov et al 2014). However, even morphologically "good" species in Central Asian Eremias are often difficult to diagnose due to high ecological and geographic variation of characters and presence of numerous "intermediate" forms and populations.…”
Section: Discussionmentioning
confidence: 99%
“…The divergence of the N1 lineage may be associated with the long-standing (since the Late Pliocene) isolated position of the Ily Basin due to mountainous surroundings and a specific relatively temperate semi-arid climate, dominated by the penetration of westerly winds [97]. Moreover, recent studies have suggested that the Ily Basin may be a plausible refugium for desert herpetofauna in Central Asia [78,98,99]. Meanwhile, it should be noted that a sample (CHS825) from Bole (the Junggar Basin) is embedded in the population from the Ily Basin (number 24 in Figure 2).…”
Section: Allopatric Divergence In the Ice Agementioning
confidence: 99%